Exposure to Environmental Chemicals from Environmental Tobacco Smoking in Korean Adolescents - Jung-Eum Lee; Ah-Reum Jo; Sunho Lee; Wanhyung Lee (Toxics, 2025)
Background: Environmental tobacco smoke (ETS) exposes adolescents to various environmental toxins, potentially affecting their developmental health. However, limited research exists on the associations between ETS exposure and the bodily burdens of environmental chemicals on adolescents. This study aimed to investigate the relationship between ETS exposure and the concentration of various environmental chemicals in adolescents, utilizing urinary cotinine as an objective biomarker. Methods: Data from 828 adolescents aged 12–17 years participating in the Korean National Environmental Health Survey (KoNEHS) were analyzed. ETS exposure was assessed via self-reported questionnaires and confirmed by urinary cotinine measurements. Levels of 33 environmental chemicals, including heavy metals, polycyclic aromatic hydrocarbons (PAHs), phthalates, phenols, volatile organic compounds (VOCs), and per- and polyfluoroalkyl substances (PFASs), were measured. Statistical analyses were conducted after adjusting for covariates. Results: Adolescents exposed to ETS showed significantly higher urinary cotinine and mono-(2-ethyl-5-carboxypentyl) phthalate (MECPP) concentrations than non-exposed adolescents. Additionally, significant positive correlations were observed between urinary cotinine levels and metabolites of PAHs (NAP, OHFlu), phenols (BPA, BPS), phthalates (MMP), and VOCs (t,t-MA) after adjustments. However, ETS exposure was not significantly associated with heavy metal concentrations. Conclusions: This study described the association between ETS exposure and environmental chemicals. A trend has been identified between ETS exposure in adolescents and increased bodily concentrations of various environmental chemicals, including PAHs, phenols, phthalates, and VOCs. As adolescence is a critical developmental period of vulnerability to environmental toxins, reducing ETS exposure to protect adolescents’ health and prevent potential lifelong health effects should be emphasized. This study was based on a cross-sectional design, and some confounding factors and measurement limitations may exist. Therefore, caution is needed in interpreting causality, and further research is recommended to determine more precise causality and long-term health effects.